A eficiência relativa da gestão dos municípios atingidos pelo rompimento da Barragem I da Mina Córrego do Feijão em Brumadinho-MG em relação aos gastos públicos - Isabela Lira Gouvea Jacinto (2023)
The public sector has undergone several changes, which have increased its responsibilities. Given this, the entity collects resources from taxpayers and, through the allocative function, expends resources to meet society's needs. Amid crises (fiscal, economic, and/or financial) and market instability, the aspect of efficiency in managing public resources through the allocative function becomes necessary. In this regard, it is reiterated that climate and technological disasters also affect public accounts negatively. In the places where these events occur, public management experiences difficulties, given that they highlight the dependence on intragovernmental transfers and external resources to achieve a normal environment before the disasters. For example, we can mention the rupture of dam I at the Córrego do Feijão Mine in Brumadinho-MG, which is characterized as one of the biggest technological disasters, causing losses in the most varied dimensions. Considering these aspects, the objective of this study is to evaluate the efficiency of municipalities in managing public expenses related to those affected by the technological disaster of the collapse of Dam I at the Córrego do Feijão Mine in Brumadinho-MG. The studied population consists of 26 municipalities affected by the event, and the analysis was carried out from 2017 to 2020. To estimate the efficiency of these municipalities in managing public spending, the Data Envelopment Analysis technique was used, a model based on the variable return of scale that is output-oriented. The technical efficiency of municipalities in managing public expenditure was assessed in the agriculture, social assistance, and health functions. The results of this work about the efficiency of municipalities in managing public expenditure, in general, indicate that, for the three functions evaluated, the technical efficiency determined in the period was categorized as highly efficient (0.90 to 1.00); however, gaps and ways to optimize efficiency were identified as assessed through analysis of target and executed values. Therefore, although municipalities achieve more results (outputs) with a certain level of investment (inputs), which reflects managerial skill, it is necessary to evaluate the aspects mentioned to avoid waste of public resources. The study made it possible to identify that the dam collapse negatively affected management efficiency regarding resources applied to agriculture, social assistance, and health.